Exceptionally high performance of protonic ceramic fuel cells with stoichiometric electrolytes. Issue 12 (3rd November 2021) - Choi, Mingi; Paik, Jaedeok; Kim, Donguk; Woo, Deokyoon; Lee, Jaeyeob; Kim, Seo Ju; Lee, Jongseo; Lee, Wonyoung
Abstract : Proton conducting electrochemical cells, especially protonic ceramic fuel cells (PCFCs), are expected to be a breakthrough technology in next-generation energy conversion systems, primarily because of their high proton conductivity and low activation energy below 600 °C. Abstract : Proton conducting electrochemical cells, especially protonic ceramic fuel cells (PCFCs), are expected to be a breakthrough technology in next-generation energy conversion systems, primarily because of their high proton conductivity and low activation energy below 600 °C. However, the low chemical and physical stability of proton conducting oxides during the sintering process has resulted in a substantially lower electrochemical performance than their predictions, limiting their utilization and application. Here, we present the fabrication of a stoichiometric BaZr0.4 Ce0.4 Y0.1 Yb0.1 O3− δ (BZCYYb) electrolyte with an average grain size of ∼10 μm by controlling the chemical potential of the A-site cation, Ba, near the BZCYYb electrolyte surface during the sintering process. A stoichiometric BZCYYb-based PCFC in an anode-supported configuration exhibits 1.90 W cm −2 and 1.01 W cm −2 with an extremely low ohmic resistance of 0.060 ohm cm 2 at 650 °C and 0.082 ohm cm 2 at 550 °C, respectively, surpassing the values of all previously reported PCFCs without complicated engineering in materials and structures of other cell components.